2020
DOI: 10.1515/biol-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp Stem Cells Exhibit Osteogenic Differentiation Potential

Abstract: AbstractBone regeneration after trauma, pathologic and surgical procedures is considered a major medical challenge. Due to limitations in using conventional approaches, cell based regenerative strategies may provide an alternative option to address such issues. In the current study, we sought to determine the osteogenic potential of dental pulp stem cells (DPSCs) isolated from impacted 3rd molars. DPSCs were isolated from human dental pulp tissue (n=6) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As can be seen from the results, the (+), (c), and (c/+) fractions could successfully synthesize a mineralized matrix, chondrocyte-typical proteins as well as neuronal cell markers. These are important characteristics of DPSCs, which are frequently reported in the literature [ 150 , 151 , 152 , 153 , 154 , 155 ]. The minor differences in the respective expression profiles might be relevant when aiming at the regeneration of a specific cell type.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from the results, the (+), (c), and (c/+) fractions could successfully synthesize a mineralized matrix, chondrocyte-typical proteins as well as neuronal cell markers. These are important characteristics of DPSCs, which are frequently reported in the literature [ 150 , 151 , 152 , 153 , 154 , 155 ]. The minor differences in the respective expression profiles might be relevant when aiming at the regeneration of a specific cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, HDPSC morphology is fibroblast-like, but some of the cells changed to a cuboidal or polygonal shape in the mechanical vibration groups at 14 d. It was previously reported that DPSCs showed a fibroblastic-elongated morphology at 7 d in differentiation media [ 22 ], and other studies have reported altered polygonal morphology of DPSCs after 21 d in osteogenic differentiation media [ 23 ]. In addition, Demiray et al have shown that a polygonal morphological change can be induced by mechanical vibrations (90 Hz, 0.15 g) of mouse MSCs during osteogenesis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPSCs (5 105, between passages 3 and 6) were introduced into the HA/PLGA scaffold and maintained in DMEM culture conditions at 37 degrees Celsius before being placed in the critical-sized bone fracture of the animal model. [16]. Before placing DPSCs into the animal model's critical-sized bone lesion, they can be kept at 4°C for 24 hours without significantly losing their vitality.…”
Section: Alizarin Red Stainingmentioning
confidence: 99%